Verbal negation in Kiswahili. A journey in the labyrinth of grammar (Atti del Sodalizio Glottologico Milanese, 2019)
This work presents a description of negation in Kiswahili. After a short exposition of the morphological patterns of negation in Kiswahili, explained in the frame of the Proto-Bantu reconstruction, an analysis of possible grammaticalization paths will be attempted in order to explain: 1) the formal identity of the post-initial negation morpheme, of the negative copula and of the first person agreement marker of pre-initial negation (si); 2) the presence of a double paradigm of conditional; 3) the negative future morpheme -toin the Zanzibar variety of Kiswahili. KEYWORDS: Negation, verbal morphology, Kiswahili, Bantu languages, grammaticalization